2018
DOI: 10.3329/jbau.v16i2.37960
|View full text |Cite
|
Sign up to set email alerts
|

Performances of improved and traditional rice based jhum cultivation in a hill district of Bangladesh

Abstract: Jhum is a customary farming which is very important for the livelihood of the alpine people of Bangladesh. Total productivity of the traditional practice of jhum cultivation is very low. The study was conducted to identify the yield gap between improved and local practices in Bandarban district of Bangladesh during March to September; 2017.The experiment was laid out in randomized complete block design (RCBD) with ten replications. Improved jhum practice produced the higher yields of rice (3113kg/ha), seed cot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Our earlier study conducted in Bandarban [14] also suggests that low yields of upland rice crop in shifting cultivation led to food insecurity of a greater segment of ethnic farmers. Mahmud et al [20] suggested that improved management practices in rice replacing indigenous landraces with drought tolerant varieties might improve yield.…”
Section: Introductionmentioning
confidence: 99%
“…Our earlier study conducted in Bandarban [14] also suggests that low yields of upland rice crop in shifting cultivation led to food insecurity of a greater segment of ethnic farmers. Mahmud et al [20] suggested that improved management practices in rice replacing indigenous landraces with drought tolerant varieties might improve yield.…”
Section: Introductionmentioning
confidence: 99%